Analysis of local setup errors of sub-regions in cone-beam CT-guided post-mastectomy radiation therapy. (26th February 2020) - Zhou, Jidan; Li, Shuai; Ye, Chengwei; Shen, Konglong; Li, An; Chen, Gang; Li, Xiaoyu; Bai, Sen; Wang, Weifeng; Zhong, Renming
ABSTRACT: The purpose of the study was to quantify local setup errors and evaluate the planning target volume (PTV) margins for sub-regions in cone-beam computed tomography (CBCT)-guided post-mastectomy radiation therapy (PMRT). The local setup errors of 20 patients undergoing CBCT-guided PMRT were analysed retrospectively. Image registration between CBCT and planning CT was performed using four sub-regions of interest (ROIs): the supraclavicular area (SROI ), ipsilateral chest wall region (CROI ), ipsilateral chest wall plus supraclavicular region (SROI + CROI ) and vertebral region (TROI ). Bland–Altman analysis, correlation, local setup errors and PTV margins among these ROIs were evaluated. There was no significant consistency or correlation for registration results between the TROI and the CROI or SROI regions on any translational axis. When using the SROI + CROI as the ROI, the systematic error (Σ) and random error (σ) of the local setup errors for the CROI region were 1.81, 1.19 and 1.76 mm and 1.84, 2.64 and 3.00 mm along the medial–lateral (ML), superior–inferior (SI) and anterior–posterior (AP) directions, respectively. The PTV margins for the CROI region were 5.80, 4.82 and 6.50 mm. The Σ and σ of the local setup errors for the SROI region were 1.29, 1.15 and 0.77 mm and 1.96, 2.65 and 2.2 mm, respectively, and the PTV margins were 4.59, 4.73 and 3.47 mm. Large setup errors and local setup errors occur in PMRT. The vertebral body should not be a position surrogate for the supraclavicular region or chest wall. To compensate for the local setup errors, different PTV margins are required, even with CBCT guidance.